The epistle of Paul to the Galatians a commentary on the Greek text - Bruce, Frederick Fyvie, 1910-90 (Exeter, UK Paternoster, 1982)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Galatians -- commentaries